Evaluation of maize (Zea mays L.) genotypes as a component of integrated stem borer (Chilo partellus Swinhoe) management in coastal region of Kenya - Ajala, S.O.; Nour, A.M.; Ampong-Nyarko, K.; Odindo, M.O. (2010)
A study was conducted at six sites of Kenya Coastal region to evaluate candidate maize genotypes for inclusion in stem borer IPM package for the area. Stem borer infestation/damage during the trial period were rather low but nonetheless, significant differences were observed between the insecticide (Carbofuran) and/orBacillus thuriengiensis (Bt) treated plots and the control. Yield loss due perhaps to levels of tolerance of the genotypes varied from 7 to 23%. Generally, varietal crosses were higher yielding than the open pollinated populations with grain yield itself being primarily influenced by number of ears harvested per plot. Therefore, tendency towards prolificacy also determined the choice of ICZ5, IC92M2 and IC92M5 as possible candidates.